PENGARUH PORTOFOLIO TERHADAP TINGKAT PENGEMBALIAN DAN RISIKO INVESTASI DI BURSA EFEK INDONESIA - Andi Asirah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The risk will always be there in any investment, whether real assets and financial assets (except deposits and other risk-free investment). One way that can be done to reduce the total risk of the portfolio in such a way, by dividing the funds into a collection of securities that have a rate of return and risk are different, or commonly referred to as a diversified portfolio without sacrificing expected returns. This study aims to: (1) to identify and analyze how the influence of the stock portfolio to the level of risk and return on investment in the capital market. (2) to identify and analyze the contribution of the portfolio effect significant effect on the rate of return and investment risk in several companies listed on the Indonesia Stock Exchange. The analytical method used in this research is simple regression testing the hypothesis with test data. The technique of collecting data through observation and documentation. The population in this study are publicly traded companies listed on the Indonesia Stock Exchange. While the sample is ten publicly traded company listed on the Indonesia Stock Exchange, namely data on stock prices over a period of five years (2004-2008). This study examined the effect of the portfolio on the return and investment risk in Indonesia Stock Exchange. Where R2 (coefficient of determination) is used to measure the amount or proportion of the contribution of independent variables to fluctuations in the dependent variable. The greater the value of R2, the greater the variation of the dependent variable is determined by a variety of independent variables. Results taccount (X)> ttable with significance level (0.005) it menas Ho refused and Hi accepted